Polarity-Dependent Driving Scheme for Suppressing Oil Film Splitting in Electrowetting Displays - Jiashuai Wang; Xianyue Wu; Yibin Lin; Zichuan Yi; Mouhua Jiang; Yiting Rui; Liangyu Li; Li Wang; Xiuxiu Li; Liming Liu; Guofu Zhou (Micromachines)
Electrowetting displays (EWDs) face challenges such as oil film splitting and luminance fluctuations, hindering stable display performance. This study employed a high-precision three-dimensional simulation model to investigate and validate oil film splitting mechanisms. The model enabled detailed optimization of a new two-stage driving scheme, integrating a sinusoidal directing (SD) and a gradient asymmetrical alternating current (GAAC) driving scheme. The proposed scheme significantly suppressed oil film splitting, reduced luminance variance by 72.3% compared to traditional methods, and improved luminance stability by 41.6%. These findings highlight the potential of simulation-driven approaches to enhance EWD performance and expand applications of microfluidic technologies.